Rapid amplification of Mycobacterium tuberculosis DNA on a paper substrate. Issue 61 (13th June 2016) - Shetty, Prasad; Ghosh, Dipayan; Singh, Minakshi; Tripathi, Aparna; Paul, Debjani
Abstract : We have amplified DNA from Mycobacterium tuberculosis on a paper substrate in 10 minutes using helicase dependent amplification technique. Abstract : We have amplified an 84 bp fragment from the insertion sequence IS6110 of Mycobacterium tuberculosis (MTB) DNA on a paper substrate in 10 min. Tuberculosis (TB) is a highly infectious disease with a high mortality rate in the developing countries. Cheap and rapid screening assays are needed at the point of care for timely intervention and treatment. While PCR-based detection of TB is faster than bacterial culture and more specific compared to microscopy, PCR is not viable as a routine screening test in many low-income countries where TB is endemic due to the requirement of an expensive thermocycler. Disease screening based on isothermal amplification techniques is, therefore, being explored as an alternative to PCR. Successful isothermal amplification of DNA from HIV, H1N1, Chlamydia trachomatis, E. coli, etc. on cheap and disposable paper substrates has been reported in the literature. Isothermal amplification of MTB DNA on paper has been challenging due to the high GC content (65%) of MTB genome. Here we report helicase dependent amplification of a fragment of MTB DNA on a paper substrate in 10 min starting from 100 copies of the template using inexpensive heat sources, such as hot plates and hand warmers. The enzyme mix used to amplify DNA can be spotted and stored dry on paper at ambient temperatures for more than a month. The DNA amplified on paper can be detected by incorporating a suitable fluorescence marker in the reaction mixture or by directly loading the paper in a standard gel electrophoresis set up. Finally, as a surrogate to real clinical sputum samples, MTB DNA was successfully amplified on paper in the viscous environment of artificial sputum.